Study of the sorting pattern of dredger fill under artificial disturbance based on the concealment degree - Yuan Yanzhao; Zhai Juyun (Scientific Reports, 2022)
Abstract This paper focuses on the sorting pattern of silt deposited at estuaries under artificial disturbance based on the concept of bidirectional concealment, which is introduced for such silt with similar particle size, low disturbance exposure angle, and difficult sorting. By establishing the relationship among the absolute concealment (Δi), the drag force coefficient ( $${C}_{D}$$ C D ), and the lift force coefficient ( $${C}_{L}$$ C L ) of highly concealed silt particles under disturbance and considering the concepts of disturbance intensity, disturbance direction, and particle concealment degree, the contribution equation for the effective depth (Y) of artificial disturbance in the deposited slurry is introduced, and the mechanical equation for the internal disturbance of silt is established. On this basis, the motion initiation probability for fine particles ( $${ε }_{{d}_{i}}$$ ε d i ) is calculated using the Shields parameter ( $$Θ$$ Θ c), and the theoretical model of plastic sandy silt sorting under artificial disturbance is derived from the Markov chain-based three-state transition. The method proposed in this paper can explain the bedload gradation of sandy silt under internal physical disturbance. The calculated data in this paper agrees well with that of the flume test on uniform sandy silt and the related sediment particle theories. Therefore, the clay particle transport pattern model in slurry under artificial disturbance based on the bidirectional concealment degree can explain the gradation changes of flow-plastic sandy silt under artificial disturbance, thus providing a theoretical basis for the research on the sorting of flow-plastic sandy silt under artificial disturbance.